Privacy Regulation and Targeted Advertising: Evidence from Apple's App Tracking Transparency - Guy Aridor; Yeon-Koo Che (Center for Economic Studies and ifo Institute (CESifo), 2024)
We use a novel dataset of online advertiser performance and product sales to quantify the medium-term economic effects of Apple's App Tracking Transparency Policy (ATT). We find that ATT significantly degraded the ability by Facebook advertisers to target advertisements based on its off-platform data. A within-advertiser comparison reveals that conversion-optimized advertisements, for which such data is crucial for targeting, suffered a 37.1% reduction in click-through rates, compared with clicks-optimized advertisements that depend less on such data, indicating a significant fall in the relevance of the former ads as perceived by users. Although advertisers did appear to substitute away from Facebook for the Google ecosystem, those with higher baseline dependence on Facebook experienced difficulty in customer acquisition, receiving 26.2% fewer orders from new customers.
Keywords: 330; privacy; app tracking transparency; online advertising; privacy regulation; social media